Gender in Bolivian Production : Reducing Differences in Formality and Productivity of Firms - World Bank (World Bank, 2012)
A main goal of this study is to determine the variables responsible for the lower formality of women-owned businesses. The companion study (the World Bank 2007a) shows that Bolivia's informal sector is the largest in Latin America by many definitions and measures. It also provides a rationale for promoting formality given the many negative effects of a high rate of informality. These negative effects include a lower growth potential as informal firms tend to be less productive owing to limited access to physical, financial, and human capital, and a smaller scale of operations; negative fiscal impacts as informal firms "free ride" on services provided with fiscal resources; and negative social externalities, including weaker rule of law and public institutions, increased corruption, and weakened ability to enforce contracts. A second goal of this study is to identify gender-based productivity constraints that hinder the growth of female-owned businesses. First, author's analysis of the impact of formality on profitability shows that the gains of formalization for most female-owned businesses increase as the firms grow. Second, author's find that the smaller scale of operation of female-owned firms is one of the main causes of gender-based differences in productivity and profitability. However, most of the differences between male and female-owned firms diminish or disappear as firms grow.